Ginkgo biloba extract (EGb 761) attenuates oxidative stress induction in erythrocytes of sickle cell disease patients - Aline Emmer Ferreira Furman; Railson Henneberg; Priscila Bacarin Hermann; Maria Suely Soares Leonart; Aguinaldo José do Nascimento (Universidade de São Paulo, 2012)
Sickle cell disease promotes hemolytic anemia and occlusion of small blood vessels due to the presence of high concentrations of hemoglobin S, resulting in increased production of reactive oxygen species and decreased antioxidant defense capacity. The aim of this study was to evaluate the protective action of a standardized extract of Ginkgo biloba (EGb 761), selected due to its high content of flavonoids and terpenoids, in erythrocytes of patients with sickle cell anemia (HbSS, SS erythrocytes) subjected to oxidative stress using tert-butylhydroperoxide or 2,2-azobis-(amidinepropane)-dihydrochloride, in vitro. Hemolysis indexes, reduced glutathione, methemoglobin concentrations, lipid peroxidation, and intracellular reactive oxygen species were determined. SS erythrocytes displayed increased rates of oxidation of hemoglobin and membrane lipid peroxidation compared to normal erythrocytes (HbAA, AA erythrocytes), and the concentration of EGb 761 necessary to achieve the same antioxidant effect in SS erythrocytes was at least two times higher than in normal ones, inhibiting the formation of intracellular reactive oxygen species (IC50 of 13.6 µg/mL), partially preventing lipid peroxidation (IC50 of 242.5 µg/mL) and preventing hemolysis (IC50 of 10.5 µg/mL). Thus, EGb 761 has a beneficial effect on the oxidative status of SS erythrocytes. Moreover, EGb 761 failed to prevent oxidation of hemoglobin and reduced glutathione at the concentrations examined. A doença falciforme promove anemia hemolítica e oclusão dos pequenos vasos, causados pela presença de altas concentrações de hemoglobina S, cujas consequências incluem a produção aumentada de espécies reativas de oxigênio e diminuição da capacidade de defesa antioxidante. O objetivo desse estudo foi avaliar a ação protetora de um extrato padronizado de Ginkgo biloba (EGb 761), selecionado devido ao seu alto conteúdo de flavonóides e terpenóides, em eritrócitos de pacientes com anemia falciforme (HbSS, eritrócitos SS) submetidos ao estresse oxidativo usando terc-butil-hidroperóxido e 2,2-azobis-(amidinopropano)-diidrocloreto, in vitro. Índices de hemólise, glutationa reduzida, concentração de metemoglobina, peroxidação lipídica e espécies reativas de oxigênio foram determinados. Eritrócitos de pacientes com anemia falciforme apresentaram taxas aumentadas de oxidação da hemoglobina e peroxidação lipídica e a concentração de EGb 761 necessária para atingir o mesmo efeito antioxidante foi pelo menos duas vezes maior em relação aos eritrócitos normais (HbAA, eritrócitos AA), inibindo a formação de espécies reativas de oxigênio (IC50 de 13.6 µg/mL), prevenindo parcialmente a peroxidação lipídica (IC50 de 242.5 µg/mL) e prevenindo a hemólise (IC50 de 10.5 µg/mL). Portanto, EGb 761 possui um efeito benéfico no estado oxidativo dos eritrócitos SS. Entretanto, o EGb 761 não preveniu a oxidação da hemoglobina e da glutationa reduzida, nas concentrações examinadas.